EFL Learners’ Perception of Using ChatGPT as a Supporting Tool for Academic Writing: Benefits and Challenges - Maghfiroh, Tiffani Gea; Suvi Akhiriyah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study investigates EFL learners’ perceptions of using ChatGPT as a supporting tool for academic writing, focusing on both its benefits and challenges. The research was motivated by the increasing integration of AI in education and the persistent difficulties faced by students in academic writing. The study employed a quantitative descriptive survey method, targeting 298 English Language Education students from the 2021 and 2022 cohorts at a state university in Surabaya. A purposive sample of 74 respondents completed a closed-ended questionnaire adapted from previous validated instruments. Data were analyzed using descriptive statistics in SPSS. The results show that most students perceive ChatGPT as highly beneficial for idea generation, organization, and language accuracy, but also report significant challenges such as off-topic responses, difficulty maintaining originality, and uncertainty about information accuracy. The findings highlight the need for critical engagement and responsible use of AI tools. Future research should expand the sample and employ qualitative approaches to deepen understanding. Practically, educators should guide students in balancing technological support with independent writing skills.